KEPEMIMPINAN TRANSFORMASIONAL DALAM MENGEMBANGKAN LINGKUNGAN BELAJAR YANG POSITIF DI SD NEGERI 7 TALANG UBI - Ria Adien; Edi Zalharis; Muhammad Sirozi (LP2M IAIN Sultan Amai Gorontalo, 2025)
This research is motivated by the essential role of the school principal as a transformational leader in creating a conducive, collaborative, and character-oriented learning environment. The purpose of this study is to analyze how the principal’s transformational leadership contributes to developing a positive learning environment at SD Negeri 7 Talang Ubi, Penukal Abab Lematang Ilir Regency. This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and school staff. The findings reveal that transformational leadership is implemented through four key dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The principal successfully fosters a culture of mutual respect, encourages teacher innovation, and nurtures a collective spirit in learning. The impact of this leadership is evident in increased discipline, motivation, and a more positive school climate. These findings are expected to contribute theoretically to educational leadership development and serve as a practical reference for principals to create a harmonious and productive learning environment. Keywords: Transformational leadership; Learning environment; Teacher motivation.